Professional Training in Early Intervention for Children and Families in Russian Federation - Mukhamedrahimov, R.Z.; Samarina, L.V. (Bulletin of Practical Psychology of Education, 2020)
In accordance with the Concept for the Development of Early Care in the Russian Federation (Decree of the Government of the Russian Federation of 2016, December 17, No. 2723-r), the creation of an early intervention system for children from birth to three years old and their families is an integral part of the formation of comprehensive assistance to children with health disabilities. One of the priority tasks of the Concept implementation is the management of the quality of services, including through the creation of a system for training professionals in the field of early intervention. The article analyzes the need for professionals specializing in providing early intervention in the constituent entities of the Russian Federation, as well as the directions and content of their training. In addition, information is provided on domestic and foreign experience of professional training of such experts. The results of the analysis indicate the need to create a variable system for training professionals in the field of early intervention in the Russian Federation. Training offers include activities in the field of higher and further professional education, including retraining and advanced training. The authors emphasize the need to combine professional training in selected areas of early care — with the training of transdisciplinary professionals. В соответствии с Концепцией развития ранней помощи в Российской Федерации (постановление Правительства РФ от 17.12.2016 г. № 2723-р), создание системы ранней помощи детям от рождения до трех лет и их семьям является неотъемлемой частью формирования системы комплексной помощи детям с ограниченными возможностями здоровья, в том числе детяминвалидам. Одной из приоритетных задач реализации Концепции является управление качеством услуг, в том числе — за счет создания системы подготовки профессионалов в сфере ранней помощи. В статье анализируется потребность в профессионалах, специализирующихся на оказании ранней помощи, в субъектах РФ, а также направления и содержание их подготовки. Кроме того, приводится информация об отечественном и зарубежном опыте профессиональной подготовки подобных экспертов. Результаты анализа свидетельствуют о необходимости создания в РФ вариативной системы подготовки профессионалов в сфере ранней помощи. Предложения по подготовке включают мероприятия в области высшего и дополнительного профессионального образования, в том числе переподготовки и повышения квалификации. Авторы подчеркивают необходимость сочетания профессиональной подготовки в отдельных областях ранней помощи — с подготовкой профессионалов трансдисциплинарной направленности.